Sparing Saphenous Vein During Inguinal Lymphadenectomy in Patients with Vulvar Cancer: A Single Center Experience of 10 Years - Özat, Mustafa; Kanat Pektaş, Mine; Güngör, Tayfun; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: The present study aims to investigate the short-and long-term morbidity associated with the preservation of saphenous vein during inguinal lymphadenectomy in patients with vulvar cancer. STUDY DESIGN: A retrospective analysis was conducted in a total of 108 women who were diagnosed with vulvar cancer. The women undergoing preservation versus ligation of saphenous vein during inguinal lymphadenectomy were compared with respect to recurrence, disease-free survival, short and long term complications. RESULTS: Saphenous vein was spared in 88 inguinal incisions made in 51 women while saphenous vein was ligated in 101 inguinal incisions made in 57 women. When compared with those undergoing saphenous vein ligation, the short-term and long-term complications were significantly less frequent in women whose saphenous veins were spared (22.5% vs 42.4%, 12.7% vs 35.0% respectively; p<0.05). However local and lymphatic recurrence rates were comparable in women undergoing either preservation or ligation of saphenous vein during inguinal lymphadenectomy (19.3% vs 22.2%, 9.8% vs 10.5% respectively; p>0.05). The incidence of wound breakdown, local infection and chronic lymphedema were significantly lower in women undergoing saphenous vein preservation (0% vs 25.0%, 1.2% vs 38.3%, 11.6% vs 44.4% respectively; p<0.05). The existence of lymphatic involvement was found to be unassociated with the risk of acute or chronic lymphedema. CONCLUSIONS: The preservation of saphenous vein during inguinal lymphadenectomy reduces the incidence of short-term and long-term complications without affecting the risk of local recurrence. Depending on the experience of the surgeon, the surgical strategy should be individualized and optimized for each patient with vulvar cancer.